2020
DOI: 10.17691/stm2020.12.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Nutritional Status and Spirometric Parameters in Children with Bronchial Asthma

Abstract: The potential mechanisms of bronchial asthma (BA) negative modification under the influence of obesity are currently being actively studied. However, at present, the effect of nutritional status on bronchial obstruction in children with BA cannot be considered established. In this regard, the purpose of this work was to study the relationship of spirometric parameters reflecting bronchial patency with nutritional status in children with asthma.Materials and Methods. The study involved 54 patients with BA at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
1
0
0
1
Order By: Relevance
“…Our data are consistent with the results obtained by the research groups Khrisanapant et al [16], Xu et al [17], and Han et al [18], who also note that as BMI increases, the ratio of FEV 1 /FVC is observed in children and adolescents with BA [19]. The results obtained are also consistent with our pilot study [20].…”
Section: Discussionsupporting
confidence: 93%
“…Our data are consistent with the results obtained by the research groups Khrisanapant et al [16], Xu et al [17], and Han et al [18], who also note that as BMI increases, the ratio of FEV 1 /FVC is observed in children and adolescents with BA [19]. The results obtained are also consistent with our pilot study [20].…”
Section: Discussionsupporting
confidence: 93%
“…Allergology and Immunology in Pediatrics. 2022; 2: 50-52. https://doi.org/10.53529/2500-1175-2022-2-50-52 Вступление В настоящее время продемонстрировано, что ожирение оказывает неблагоприятное влияние на течение бронхиальной астмы (БА), включая негативное воздействие на параметры внешнего дыхания [1,2].…”
unclassified